A Managerial Guide For Understanding Occupational Health And Safety Legislation - Gallina, Paul Leonard (European Scientific Journal, ESJ, 2016)
This paper is a descriptive attempt to provide managerial understanding of occupational health and safety legislation. As such it takes a comparative approach dealing with statutes in Canada, USA, the EU, and Australia. The substantive content of this legislation is divided into eight areas with examples and commentary. The paper also argues that substantively there is a great deal of similarity across jurisdictions. Furthermore, the claim is made that knowledge of the legislative requirements is needed not only for effective managerial compliance strategies, but that the legislation does provide a set of best practices.